NATIVE ENGLISH TEACHERS IN EFL SPEAKING CLASSES: DEPICTING THEIR STRATEGIES TO TEACH VIETNAMESE STUDENTS - Miftahul Mahrus; Novinda Rosayanti (English Education Department, 2021)
The aims of this research are; (1) to know the strategies used by native English teachers to teach speaking to the students of Vietnam National University of Agriculture, (2) to describe how the strategies contributed to the students speaking skills, and (3) to explain the problems faced by native English teachers in EFL speaking classes. This research is descriptive research with a qualitative approach. The data were collected through classroom observation, interviews, and documentation. It presents the result of the study in the form of a descriptive explanation. The findings of this research are the strategies used by native English teachers to teach speaking to the students of Vietnam National University of Agriculture, namely (a) group discussion, (b) role play, (c) brainstorming, (d) storytelling, (e) story completion, (f) describing picture, (g) game (guessing the word), (h) using target language/interview. Based on those strategies, the results show that the strategies help students to improve their speaking skills, vocabulary, and confidence. Also, it can help students to solve problems, increase sensitivity, think critically, and express their ideas. Furthermore, the findings of the problems faced by native English teachers in speaking class are (a) pronunciation, (b) lack of confidence, (c) lack of ending sounds, (d) no vocabulary and grammar.